Living on the city: Records of night monkeys (Aotus spp.) in urban and peri-urban forests of Colombia - Montilla, Sebastián O.; Pulido-G, Anny; Montoya Valencia, Stiven; Diosa, Dayanna; Niño-Moreno, Margarita; Lozano Frias, Maria Fernanda; Camacho-Duran, Maria José; Toro-Soto, Manuela; Chavarro, Luisa F.; Gómez-Hoyos, Diego A.; Arcila-Pérez, Luisa F. (THERYA, 2025)
Urbanization has transformed natural habitats by concentrating human populations in urban areas, with important consequences for biodiversity. In Colombia, several mammals, including primates, have occupied urban areas in different regions of the country. The objective of this study is to compile information on night monkeys (Aotus spp.) in urban and peri-urban forests in Colombia, based on field records and literature review. We compiled our own and literature records of night monkeys from urban and peri-urban forests in Colombia between 2018 and 2024. We categorized these records by type and grouped them by night monkey species, geographic location, type of population center (departmental capital city, municipality, corregimiento and vereda), and proximity to urban infrastructure. 36 localities were identified (23 new and 13 from the literature), distributed in 11 departments, ranging from the capital city to the veredas, where night monkeys have been recorded in urban and peri-urban areas. The most abundant species was A. lemurinus, and we report the first urban and peri-urban records of A. brumbacki, A. griseimembra and A. vociferans. About 33 % of the records of night monkeys in urban and peri-urban forests were found in capital cities with a population of more than 100000 people. Additionally, we report the use of 3 artificial sleeping sites in urban and peri-urban forests by A. brumbacki, A. griseimembra and A. vociferans groups. Records were also found in educational institutions such as schools and universities, suggesting the possibility of establishing long-term studies with these night monkeys as flagship species. The monitoring of these primates in urban and peri-urban environments is crucial for their conservation and to guide public policies towards sustainable development, especially in the management of urban threats such as electrocution, which remains a significant problem.